Symtoms experienced and practices adopted by menopausal woman in the age group 45-56 years in a peri urben Community. - Wijesekara, L.C (My University, 2003)
The overall prevelence of experiencing one or more of the selected symptoms was 44.5 .However the experience of symptoms ever was 58.2 . Symptoms were more prevelent among women in younger age group with low educational qualifications and with poor knowledge on menopause. Majority of symptoms were perceived either as not had adopted home remedy only, while a considerable propotion (24.troublesome or troublesome to some extent. Majority of woman (28.17} had taken indigenous tretement .western tretement only (15.) was taken up as next.This study revealed that knowledge on menopause, a factor which could be changed by health education, increases experiences of symptoms and the tretement seeking behavior.Therefor it is recommended that health education programmes directed at menopausal women shoud be conducted.